In-vitro antihelminthic activity of alcoholic extract from Paullinia pinnata Linn against Ascaris suum - Nyasinge, Joanitah; Montero, Genny Domínguez; Valladares, Miriela Betancourt; Noah, Joseph Openy Oweta; Nkwangu, David (Revista Cubana de Plantas Medicinales, 2018)
Introduction: Medicinal plants are used both for the treatment of certain conditions and to preserve health and vitality. According to estimates by the World Health Organization, 80% of the world population, excluding industrialized countries, rely on traditional medicine, particularly medicinal plants. Several parts of the plant Paullinia pinnata Linn have been used by many African tribes to treat a variety of conditions, including helminthiases. Objective: Evaluate the antihelminthic effect of P. pinnata alcoholic leaf extract against Ascaris suum. Methods: Dry leaves of P. pinnata were used to obtain the 23.33 % alcoholic extract, which then underwent phytochemical analysis. Thirty Ascaris suum worms were divided into 6 groups: 2 control, 1 negative and 1 positive, and 4 experimental. The experimental groups were exposed to different concentrations of the alcoholic extract (5, 10, 40 and 80 mg/ml). Goodwin's physiological solution was used as negative control, whereas the positive control was albendazole 40 mg/ml. Motility testing was performed to determine the antihelminthic activity of the plant, and the mortality rate was estimated. The chi-square test was applied, and a p value below 0.05 was considered to be significant. Results: Saponins, alkaloids, flavonoids, tannins and triterpenoids were all found in the alcoholic extract of P. pinnata. The plant showed significant antihelminthic activity, and mortality rates were higher than those obtained with albendazole. Conclusions: Saponins, alkaloids, flavonoids, tannins and triterpenoids may be responsible for the antihelminthic activity of the study alcoholic extract, which was greater than that of albendazole
Keywords: Paullinia pinnata Linn; Albendazole; Antihelminthic activity; Motility; Mortality rate